Link and Match Program with Business and Industry (DU/DI) As An Effort for Placement of Graduates at SMK Muhammadiyah Delanggu - Khasanah, Uswatun (Journal of Islam and Science, 2020)
This research is qualitative research with a case study approach. The data sources used were words and actions as well as written sources. The techniques of research subject collection were purposive sampling and snowball sampling. The data collection techniques chosen were observation, interview, documentation, and triangulations. Data validity testing techniques included triangulation of technical resources. The data were analyzed using interactive analysis techniques in the form of data reduction, data presentation, and conclusion drawing/ verification. Based on the research findings, the implementation of the link and match program starts from the preparation/ planning stage, the implementation of the teaching and learning process in schools and the cooperation with the industry, and the evaluation stage. The supporting factor for the link and match is the cooperation between the school and DU/DI. In addition, there are a positive responses from students, parents, DU/DI, and the government. There are wo inhibiting factors of the link and match, namely internal and external factors. The solutions used to overcome the problems that occurred are (a) the school always provides supplies and maximizes the practice unit; (b) the school tries to maximize the existing curriculum with work processes in industry so as not to deviate from the core competencies or basic competencies (KI/KD) determined by the Education Office.